Work-family guilt of collegiate athletic trainers: a descriptive dtudy - Eason, C. M.; Singe, S. M.; Rynkiewicz, K. (International Journal of Athletic Therapy & Training, 2020)
Work-family guilt (WFG) is a measure used to assess guilt related to work interference with family and family interference with work. While work-family conflict (WFC) has been studied in the athletic trainer (AT) population, WFG has not. The purpose of this study was to gather descriptive data on WFG and to determine if WFC can predict WFG. There were significant positive associations between WFG and hours worked, but no sex differences in WFG or WFC exist. WFG was predicted by WFC. Results indicate higher levels of WFG and WFC are associated with a greater number of hours worked. Because guilt can negatively impact overall health, steps should be taken to mitigate WFC and WFG.